2016
DOI: 10.3390/proteomes4020016
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Based Proteomics Reveals Heterogeneous Kinome and ATP-Binding Proteome Responses to MEK Inhibition in KRAS Mutant Lung Cancer

Abstract: One way cancer cells can escape from targeted agents is through their ability to evade drug effects by rapidly rewiring signaling networks. Many protein classes, such as kinases and metabolic enzymes, are regulated by ATP binding and hydrolysis. We hypothesized that a system-level profiling of drug-induced alterations in ATP-binding proteomes could offer novel insights into adaptive responses. Here, we mapped global ATP-binding proteomes perturbed by two clinical MEK inhibitors, AZD6244 and MEK162, in KRAS mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…The findings of the study by Kim et al. align with MEK‐inhibitors having been previously reported as inducing protective autophagy in KRAS mutant non‐small cell lung cancer (NSCLC), and suggests that upregulation of autophagy in KRAS mutant lung cancer may be kinase dependent . When validated, this may provide a reasonable basis for combination chemotherapy with kinase inhibitors.…”
Section: Whole Cell Proteomics Analysissupporting
confidence: 63%
See 2 more Smart Citations
“…The findings of the study by Kim et al. align with MEK‐inhibitors having been previously reported as inducing protective autophagy in KRAS mutant non‐small cell lung cancer (NSCLC), and suggests that upregulation of autophagy in KRAS mutant lung cancer may be kinase dependent . When validated, this may provide a reasonable basis for combination chemotherapy with kinase inhibitors.…”
Section: Whole Cell Proteomics Analysissupporting
confidence: 63%
“…Cells were treated with two MEK‐inhibitors, lysed, and the ATP‐binding kinome enriched, using a kinase enrichment kit, for subsequent digestion and LC‐MS/MS analysis. The study found that changes in the ATP‐binding proteome were cell type dependent and not KRAS mutation dependent . Furthermore, p53/LKB1 status was not determined to be a major factor in changes in the ATP‐binding proteome.…”
Section: Whole Cell Proteomics Analysismentioning
confidence: 89%
See 1 more Smart Citation
“…Small-molecule inhibitors that target protein kinases in the RAS pathway have been developed and are FDA approved (1). However, potential resistance to inhibition of KRAS signaling can involve mutations in targets or activation of compensatory mechanisms (28)(29)(30). Inhibiting multiple pathways concurrently with the MEK and AKT inhibitors, AZD6244 and MK2206, respectively, successfully abrogates tumor growth in preclinical models (31).…”
Section: Discussionmentioning
confidence: 99%
“…Chemical biology methods to measure kinase activation rely on the assumption that only active kinases may bind to either ATP or kinase inhibitors immobilised on beads (e.g. kinobeads and multiplex kinase inhibitor beads ).…”
Section: Approaches To Identify Regulatory Kinasesmentioning
confidence: 99%